2012
DOI: 10.4101/jvwr.v5i1.2151
|View full text |Cite
|
Sign up to set email alerts
|

Between Purpose and Method: A Review of Educational Research on 3D Virtual Worlds

Abstract: This study aims to enhance our holistic understanding of 3D virtual worlds by providing a detailed analysis of the research methods and research trends related to the research of 3D virtual worlds for educational environments. Data was collected by searching for the ubiquitous term, "virtual world," from databases. Snowball sampling was also employed. The researchers critically analyzed the literature as data focusing on how virtual worlds were applied in individual studies, what research methods were used, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 25 publications
1
39
0
Order By: Relevance
“…A majority of the authors are located in the UK and the USA and several aspects of virtual worlds are covered in the issues. See also literature reviews on virtual worlds in education (Conole & Alevizou, 2010;Hew & Cheung, 2010;Inman, Wright, & Hartman, 2010;Kim, Lee, & Thomas, 2012;Savin-Baden et al, 2010;Wang & Burton, 2013). Some of these reviews not only report empirical studies, but encompass a range of sources.…”
Section: Teaching In Virtual Worldsmentioning
confidence: 99%
See 2 more Smart Citations
“…A majority of the authors are located in the UK and the USA and several aspects of virtual worlds are covered in the issues. See also literature reviews on virtual worlds in education (Conole & Alevizou, 2010;Hew & Cheung, 2010;Inman, Wright, & Hartman, 2010;Kim, Lee, & Thomas, 2012;Savin-Baden et al, 2010;Wang & Burton, 2013). Some of these reviews not only report empirical studies, but encompass a range of sources.…”
Section: Teaching In Virtual Worldsmentioning
confidence: 99%
“…A dominating theme of interest in previous literature concerns the possibilities virtual worlds have in an educational context (Annetta, Folta, & Klesath, 2010;Conole & Alevizou, 2010;Deutschmann, 2012;Esteves, Fonseca, Morgado, & Martins, 2011;Inman, Wright, & Hartman, 2010;Kim, Lee, & Thomas, 2012;Petrakou, 2010;Rapanotti, Minocha, Barroca, Kamel Boulos, & Morse, 2012;Wang & Burton, 2013). Several concepts are used in these studies when describing this interest, such as opportunities, affordances, potentials, facilitations and strengths.…”
Section: Teaching In Virtual Worldsmentioning
confidence: 99%
See 1 more Smart Citation
“…2. Kim et al (2012) found sixteen reports describing the use of SL in foreign language courses, eight in computer education, eleven in general education, twelve in the sciences, five in interdisciplinary education, three in economics, two in design, and eight in other disciplines.…”
mentioning
confidence: 99%
“…See Kim et al 2012: 2. Herold's (2012) report of his experience using SL at Hong Kong Polytechnic University is a helpful study, as is Calvert-Minor 2011.…”
mentioning
confidence: 99%